2011
DOI: 10.1186/1748-717x-6-44
|View full text |Cite
|
Sign up to set email alerts
|

[18F]fluoroethylcholine-PET/CT imaging for radiation treatment planning of recurrent and primary prostate cancer with dose escalation to PET/CT-positive lymph nodes

Abstract: BackgroundAt present there is no consensus on irradiation treatment volumes for intermediate to high-risk primary cancers or recurrent disease. Conventional imaging modalities, such as CT, MRI and transrectal ultrasound, are considered suboptimal for treatment decisions. Choline-PET/CT might be considered as the imaging modality in radiooncology to select and delineate clinical target volumes extending the prostate gland or prostate fossa. In conjunction with intensity modulated radiotherapy (IMRT) and imaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 11 publications
2
41
0
1
Order By: Relevance
“…In the overall population, the disease-free survival rate was 56%, whereas in patients treated with metastasis-directed S-RT, the disease-free survival rate was 80%. Similar results were reported by Würschmidt et al (29) for recurrent PCa in 19 patients treated with intensity-modulated radiotherapy for BCR after RP. A standard dose was delivered to the prostatic bed with a boost (65 Gy) for 18 F-choline PET/CT-positive lymph nodes.…”
Section: Use Of Choline Pet/ct To Guide Metastasis-directed S-rtsupporting
confidence: 80%
“…In the overall population, the disease-free survival rate was 56%, whereas in patients treated with metastasis-directed S-RT, the disease-free survival rate was 80%. Similar results were reported by Würschmidt et al (29) for recurrent PCa in 19 patients treated with intensity-modulated radiotherapy for BCR after RP. A standard dose was delivered to the prostatic bed with a boost (65 Gy) for 18 F-choline PET/CT-positive lymph nodes.…”
Section: Use Of Choline Pet/ct To Guide Metastasis-directed S-rtsupporting
confidence: 80%
“…Conversely, patients in whom distant metastases or locoregional LN involvement is suspected may not benefit from S-RT: they are usually treated with ADT regardless of the site of recurrence. Recently, it was suggested that aggressive therapeutic approaches in PCa patients with proven distant recurrence could be feasible and increase the biochemical free survival (12)(13)(14). PET/CT using 11 Cor 18 F-labeled choline may have a role in this scenario (15).…”
mentioning
confidence: 99%
“…Wurschmidt et al treated PET/CT positive lesions in lymph nodes with 66.6 Gy [16]. However, in direct contrast, in the study by Casamassima et al the lymph node lesions detected with an 11 C-choline PET/CT scan, were treated with 50 Gy in 25 fractions plus 24 Gy in an additional boost [9].…”
Section: Discussionmentioning
confidence: 99%